Hermeneutics in Islamic Studies at Western World : History, Theory and Implications - Abdullah Muslich Rizal Maulana; Firda Khoirun Nisa; Rohmah Akhirul Mukharom; Dyah Ayu Rejekiningtya (Indonesian Journal of Islamization Studies, 2024)
This article aimed to elaborate on ‘Hermeneutics’ as a Discourse in Postmodern Worldview; emerged in the Christian theological system, advanced then reached its peak in the Postmodern era. Hermeneutics later did not merely develop itself within Christianity but implied several consequences to Islamic Studies. In order to come deep into the discussion, this research used the ‘Content Analysis’ method in the form of ‘Qualitative Research’, revealing the nature of Hermeneutics as the discourse of Worldview, altogether with its impact on Islamic Studies. This article concluded that Hermeneutic is classified as a discourse based on the Western-Postmodern Worldview with some historical background and theoretical framework and implications towards Islamic Studies, especially in regards to the Qur’an.